Implementation of Child-Friendly City Program Policy by Department Women and Children Empowerment Service Pekanbaru - Syukri, Muhammad; Prihatin, Panca Satyo (CV. Austronesia Akademika, 2024)
In supporting the success of the legislation on child protection, the government is implementing the Child-Friendly City/District (KLA) program across Indonesia. Based on the development of the Child-Friendly City program implemented in Pekanbaru, issues concerning child protection are still relatively low. This is due to Pekanbaru being one of the major cities that has experienced rapid changes and development on the island of Sumatra. The development of Pekanbaru has attracted many individuals seeking better livelihood opportunities in the city. The objective of this study is to examine the implementation of the child-friendly city program policy by the Office of Women's Empowerment and Child Protection in Pekanbaru, as well as the factors impeding its effectiveness. The research employs a descriptive quantitative method, with data collection conducted through interviews, observations, questionnaires, and documentation. The key informant for this study is the Head of the Office of Women's Empowerment and Child Protection of Pekanbaru. Meanwhile, the other informants include the Head of the Child Protection and Empowerment Division, the Head of the Regional Planning Agency, the Chairman of the Women and Child Protection Integrated Service Center (P2TP2A), and the Child Forum of Pekanbaru. The results of the study indicate that, based on the research findings and analyses conducted by the author, the implementation of the child-friendly city program by the Office of Women’s Empowerment and Child Protection in Pekanbaru is considered to be inadequate. This deficiency is attributed to the high number of reported cases handled by the Office, which serves as the agency responsible for addressing and mitigating violence against women and children